The Influence of Brand Image and Marketing Mix on Customer Loyalty through Customer Satisfaction as an Intervening Variable at Kafe Titik Akhir Jakarta - Pangestu Raharjo; Kumba Digdowiseiso (Budapest International Research and Critics University, 2022)
This research aims to find out and analyze the Influence of Brand Image and Marketing Mix on Customer Loyalty through Customer Satisfaction as an Intervening Variable at Kafe Endpoint Jakarta. The research sample of 100 customers of Kafe End Point Jakarta. Data collection using questionnaires and STATA 16.0 is used as an analysis technique. The results of this study showed that brand image has a positive and significant effect on customer satisfaction, the marketing mix has a positive and significant effect on customer loyalty, the marketing mix has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, brand image has a positive and significant effect on loyalty. Customer satisfaction is mediated by customer satisfaction, and a marketing mix has a positive and significant effect on customer loyalty mediated by customer satisfaction.